2022
DOI: 10.1093/bib/bbab565
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive evaluation of noise reduction methods for single-cell RNA sequencing data

Abstract: Normalization and batch correction are critical steps in processing single-cell RNA sequencing (scRNA-seq) data, which remove technical effects and systematic biases to unmask biological signals of interest. Although a number of computational methods have been developed, there is no guidance for choosing appropriate procedures in different scenarios. In this study, we assessed the performance of 28 scRNA-seq noise reduction procedures in 55 scenarios using simulated and real datasets. The scenarios accounted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Current noise reduction methods for scRNA-seq data include correcting for batch effect and normalization of the sequencing data. A recent study comprehensively analyzed 28 noise-reducing methods and tools in 55 scenarios comprising of real and simulated datasets and proposed a guideline to select suitable procedures [ 38 ]. The study concluded that not a single method can be selected as generalized approach for all scRNA-seq experiments, selection of an appropriate method needs caution and depends on the study design.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Current noise reduction methods for scRNA-seq data include correcting for batch effect and normalization of the sequencing data. A recent study comprehensively analyzed 28 noise-reducing methods and tools in 55 scenarios comprising of real and simulated datasets and proposed a guideline to select suitable procedures [ 38 ]. The study concluded that not a single method can be selected as generalized approach for all scRNA-seq experiments, selection of an appropriate method needs caution and depends on the study design.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this case, reciprocal PCA model is recommended. Similarly, linear models are also sensitive to cell population imbalances, and their performance is improved by using cell groups as covariate as in scMerge [ 38 , 40 ]. By unmasking the true biological signals of interest, such methods are expected to also improve the detection of significant cis -eQTL associations in the future.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, one common limitation of the current approaches is that only simple linear relationships between modalities are captured in the model[2]. And it is hard to incorporate different types of covariates for batch effect adjustment while retaining biological variation [29, 18, 6]. Besides, it is difficult for matrix factorization algorithms to align new datasets without training on the new dataset again.…”
Section: Introductionmentioning
confidence: 99%
“…They developed a set of pipelines for single-cell processing and compared these for various analysis purposes. Their comprehensive benchmark gives the user a practical view of choices [26].…”
Section: Introductionmentioning
confidence: 99%
“…They developed a set of pipelines for single-cell processing and compared these for various analysis purposes. Their comprehensive benchmark gives the user a practical view of choices [26]. This review of recent benchmark studies highlights the importance of the discussed analysis methods in various tasks.…”
Section: Introductionmentioning
confidence: 99%